The Effect of Kegel Exercises on Perineal Wound Healing in Postpartum Mothers - Masnila Masnila; Nurlama Siregar (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study was to determine the effect of Kegel exercises on the healing of perineal wounds in postpartum mothers at the Niar Pratama Clinic and the Citra Pratama Clinic, Deli Serdang Regency. The design used in the study was a quasi-experimental method with a static group comparison, which is a type of research to determine the effect of an action on a group of subjects who received treatment, then compared it with a group that did not receive treatment. This research was conducted at the Niar Pratama Clinic and the Citra Pratama Clinic, Deli Serdang Regency which was carried out in November 2019 - November 2020. The sampling design was based on purposive sampling, namely postpartum mothers with perineal injuries of degree I. The number of samples was 60 people who received treatment 30 people, while the control group was 30 people. Data analysis was carried out after all data had been collected by re-examining all the questionnaires one by one and ensuring that all data had been filled in according to the instructions. Then provide a code for all the questions that have been asked to make it easier for researchers when tabulating and analyzing data. Data were tabulated and analyzed using the Median Test (Mann-Whitney U-Test) with a significance level of < 0.05. The results of this study are that there is a difference in wound healing in post partum mothers who do Kegel exercises when compared to mothers who do not do Kegel exercises with a difference of 18.76 points and there is an effect of Kegel exercises on perineal wound healing in postpartum mothers at the Pratama Niar Clinic and Pratama Clinic. Image of Deli Serdang Regency.